Evaluating farm household resilience and perceptions of the role of small-scale irrigation in improving adaptability to climate change stress: evidence from eastern Ethiopia - Dawid, Ibsa; Haji, Jema; Aman, Mohammed (Frontiers in Climate, 2023)
This paper surveys farmers in Kersa district, East Hararghe zone, Oromia regional state, Ethiopia, with the aim of assessing the resilience of farmers and their perceptions of the role of small-scale irrigation in improving resilience to climate change. Data were collected from a sample of 288 randomly selected households (130 adopters and 158 non-adopters). A household survey was used to gather quantitative data, and qualitative data were collected through focus group discussions and key informant interviews. Data were analyzed using principal component analysis to generate the resilience capacity index of the households. Analysis revealed that adopters were better off on all indicators of resilience, including access to food and income, assets, agricultural production, stability, and adaptive capacity. The findings also suggest that households with high resilience are more resilient to climate change. These results suggest that small-scale irrigation makes a significant contribution to farmers’ resilience and increases farmers’ resilience by minimizing the impacts of climate change through increased responsiveness to irregular weather patterns. Therefore, policymakers should pay due attention to mitigating the impacts of climate change and improving the adaptive capacity of small-scale farmers.